Metaphoric Reasoning and the Classification of eTeaching/eLearning Platforms as Supermarkets, Schools and Airports - Dobozy, Eva; Reynolds, Patricia; Schonwetter, Dieter (Association for the Advancement of Computing in Education (AACE), 2011)
This paper introduces conceptual metaphors, such as ‘supermarkets’ for LMSs, ‘schools’ for LAMS and ‘airports’ for VLE 2.0 applications, to project inferential structures and particular characteristics from familiar sources. The primary aim of this conceptualisation is to establish knowledge building through our metaphoric chain construction. The metaphoric reasoning used to characterise the selection of systems in use in selected higher education institutions at present in the Australia, the United Kingdom and Canada, provides an organisational structure that is helpful for different stakeholders. The model presented here is creating order and a tool for sense making of the current eTeaching/eLearning maze. For learning technologies to become as persuasive as they should in transforming education, complementing and replacing traditional modes of learning and teaching in the promotion of efficacy and quality, educational stakeholders must be cognisant of the range of eTeaching/eLearning platforms and their utilities.